PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN CARRD.CO TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS V SD - Rania Zahra; Nindy Profithasari; Fadhilah Khairani; Frida Destini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problem in this study was the low creative thinking ability of fifth-grade elementary school students. This study aimed to determine the effect of the Project- Based Learning (PjBL) model assisted by the carrd.co media on students’ creative thinking abilities in the IPAS subject for Grade V at SD Aisyiyah Metro Selatan. This study used a quantitative research method with an experimental type in the form of a quasi-experimental design with a nonequivalent control group design. The population in this study consisted of 61 students. The sampling technique used was saturated sampling. Data collection was carried out using a test technique in the form of essay questions. The data analysis technique used simple regression analysis. Data were collected through pretest and posttest based on indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. The results of the simple regression test showed that Fcount > Ftable, thus Ha was accepted. The results of this study indicated that the Project-Based Learning model assisted by carrd.co media had a positive and significant effect on the creative thinking ability of students in IPAS learning in grade V at SD Aisyiyah Metro Selatan.